Consumer Protection Due to Disclaimer Clause in Internet Site - Vitarani, K.; Rumawi, Rumawi (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
A unilateral agreement that contains a transfer of responsibility or known as a disclaimer clause is deemed to be in conflict with the provisions of Law No. 8 of 1999 concerning Consumer Protection in article 18, an agreement which contains limits on responsibility is also contrary to the law of agreements where this is considered to have deviated or there is no compliance or conformity with one of the conditions for the validity of an agreement, namely